Scientific literacy-based e-module in technical mechanics subject at vocational high schools - Pangastuti, Kinanti Kidung; Arthur, Riyan; Daryati (AIP conference proceedings, 2024)
This study aims to develop a scientific literacy-based e-module as teaching materials in Technical Mechanics subject at Vocational High School which can improve the vocational student’s scientific literacy skills, especially in the Construction and Property Engineering Expertise Program. The method used is research and development (R&D) with Branch’s (2009) ADDIE development model. The data was collected by distributing checklists as instruments for assessing product feasibility through validation from experts, each consisting of 3 material experts and 3 media experts. The result of product validation is analyzed using Likert Scale. Based on the product feasibility assessment, the percentage of assessment from material experts is 84.140% and the percentage of assessment from media experts is 90.790%, so that product is categorized as “very feasible” and can be used in Technical Mechanics subjects for vocational student with the Construction and Property Engineering Expertise Program.